Optimalisasi Peran Relawan Olahraga dalam Sukseskan PON Aceh-Sumut 2024: Program Pelatihan dan Pengembangan Kompetensi - ulia Hidayati Ramadhana Dian Buono; Bebi Putra Sentosa Halawa; Arman Prince Zebua; Aqila Azura; Boy Agustinus Sirait (Joska: Jurnal Isori Kampar, 2025)
Objectives: The success of major sporting events relies heavily on well-trained and competent volunteers. This community service program aimed to optimize the role of sports volunteers in supporting the XX National Sports Week (PON) Aceh-North Sumatra 2024 through comprehensive training and competency development programs. The program was conducted from March to September 2024, involving 450 volunteers across 12 venues in Medan and Aceh. Methods: The methodology included identification of training needs, development of standardized training modules, implementation of competency-based training programs, and evaluation of volunteer performance. The training covered technical skills (event management, sports officiating), soft skills (communication, teamwork, customer service), and emergency response protocols. Results: Results showed significant improvements in volunteer competency scores (pre-training average: 6.2/10, post-training: 8.7/10), enhanced event operational efficiency by 35%, and positive feedback from athletes and spectators (satisfaction rate: 92.3%). Conclusion: The program successfully created a sustainable volunteer development model that can be replicated for future major sporting events. Key challenges included coordination between different regions, language barriers, and varying baseline competency levels among volunteers. The program demonstrates the critical importance of systematic volunteer training in ensuring successful major sporting events and provides a framework for future volunteer development initiatives.